A photochemical proposal for the preparation of ZnAl2O4 and MgAl2O4 thin films from β-diketonate complex precursors. (May 2016) - Cabello, G.; Lillo, L.; Caro, C.; Seguel, M.; Sandoval, C.; Buono-Core, G.E.; Chornik, B.; Flores, M.
Graphical abstract: Highlights: ZnAl2 O4 and MgAl2 O4 thin films were prepared by photo-chemical method. The Zn(II), Mg(II) and Al(III) β-diketonate complexes were used as precursors. The photochemical reaction was monitored by UV–vis and FT-IR spectroscopy. The results reveal spinel oxide formation and the generation of intermediate products. Abstract: ZnAl2 O4 and MgAl2 O4 thin films were grown on Si(100) and quartz plate substrates using a photochemical method in the solid phase with thin films of β-diketonate complexes as the precursors. The films were deposited by spin-coating and subsequently photolyzed at room temperature using 254 nm UV light. The photolysis of these films results in the deposition of metal oxide thin films and fragmentation of the ligands from the coordination sphere of the complexes. The obtained samples were post-annealed at different temperatures (350–1100 °C) for 2 h and characterized by FT-Infrared spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), atomic force miscroscopy (AFM), and UV–vis spectroscopy. The results indicate the formation of spinel-type structures and other phases. These characteristics determined the quality of the films, which were obtained from the photodeposition of ternary metal oxides.